(untitled) (Agroindustria, Sociedad y Ambiente, 2023)
The lifestyle has changed, increasing work activities with little physical effort, based on the use of computers, likewise in the agro-industrial sector, although many physical tasks are required, during the pandemic sanitary restrictions led employees to telework with managerial, administrative and marketing positions, increasing the risks of the prevalence of obesity and health effects, due to sedentary lifestyle. To evaluate the prevalence of obesity in an agro-industrial company and its relationship with the increase in occupational risks, we worked with a sample of 80 people using the IPAQ method, lifestyle and body mass index (BMI) were determined, calculating the occupational risk associated with the incidence of diseases such as diabetes, hypertension, cardiovascular problems and metabolic syndrome. Found that there is a prevalence of overweight-obesity of 75.6% in men and 41.7% in women, presenting mostly type 1 obesity with 20 and 15% respectively due to the low level of physical activity, therefore the risks They were classified as moderate and extreme severity, respectively, which contributes to this increase in BMI and with it the probability of suffering from diabetes and cardiovascular diseases, in those workers of the agro-industrial company who teleworked during the pandemic.